Real innovation or second-best solution? First experiences from results-based aid for fiscal decentralisation in Ghana and Tanzania - Heiner Janus (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
This paper systematically records first experiences with results-based aid for fiscal decentralisationin Ghana and Tanzania. Results-based aid is an innovative aid modality that links funding to the achievement of pre-agreed results, based on a contract between the donor and the recipient country. Observations from Ghana and Tanzania show that the modality holds great potential in incentivising better performance in fiscal decentralisation compared to traditional aid approaches. Yet, a number of challenges emerge during implementation, including trade-offs between country ownership and results-orientation or increased transaction costs, for instance. Therefore, results-based aid is a promising aid modality for fiscal decentralisation, but it should be implemented in alignment with partner-country systems and harmonised with other aid modalities. Results-based aid can be one important element of the aid modality-mix in fiscal decentralisation.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Wirksamkeit und Evaluierung